Saline-alkali soil reclamation and utilization in China: progress and prospects - Guangzhou WANG; Gang NI; Gu FENG; Haley M. BURRILL; Jianfang LI; Junling ZHANG; Fusuo ZHANG (Frontiers of Agricultural Science and Engineering)
● Saline-alkali land is an important underutilized resource in China that could complement arable land and maintain the food security. ● China has made great progress in saline-alkali soil reclamation and utilization, and developed customized technologies for these soils. ● In the future, comprehensive management strategies should be implemented by integrating traditional saline-alkali soil management practices and new technologies to increase crop tolerance. Soil salinity is a global threat to the productivity of arable land. With the impact of population growth and development of social economy in China, the area of arable land has been shrinking in recent decades and is approaching a critical threshold of 120 Mha, the minimum area for maintaining the national food security. Saline-alkaline land, as important backup reserve, has been receiving increased attention as an opportunity to expand land resources. This review first summarizes the general principles and technologies of saline soil reclamation to support plant growth, including leaching salts or blocking the rise of salts, and soil fertility enhancement to improve the buffering capacity. Then the progress in this area in China is described including the customization of technologies and practices used in different saline-alkali regions. Following the soil management strategies, the concept of selecting crops for saline soil is proposed. This encompasses halophyte planting, salt-tolerant crop breeding and the application of saline-adapted functional microorganisms to improve the adaptation of crops. Finally, the current problems and challenges are evaluate, and future research directions and prospects proposed for managing this major soil constraint.